2010
DOI: 10.1057/ap.2009.23
|View full text |Cite
|
Sign up to set email alerts
|

Is this the way to Brussels? CEE civil society involvement in EU governance

Abstract: Whereas state actors from new EU member countries receive formal representation and voting rights that safeguard against their marginalisation in the system of EU governance, civil society organisations from new member states find it much harder to gain access to decision-making processes at the EU level. However, as many of them work on issues that are now (at least partly) decided at the EU level, participation in EU governance should become an integral part of their strategy. Based on a quantitative assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…This is in line with Pleines' (2010: 240) findings that only very few CSOs from new member states 384 "are physically present in Brussels for more than a couple of days a year (…), have leadership positions in European umbrella organisations or direct access to key 384 More specifically from Central and Eastern Europe (Pleines 2010) EU decision makers". This means that the views of the more active members are better reflected in advocacy positions and policy papers published by the respective CSO.…”
Section: Active Minorities and Mass Apathy?supporting
confidence: 78%
“…This is in line with Pleines' (2010: 240) findings that only very few CSOs from new member states 384 "are physically present in Brussels for more than a couple of days a year (…), have leadership positions in European umbrella organisations or direct access to key 384 More specifically from Central and Eastern Europe (Pleines 2010) EU decision makers". This means that the views of the more active members are better reflected in advocacy positions and policy papers published by the respective CSO.…”
Section: Active Minorities and Mass Apathy?supporting
confidence: 78%
“…A few studies have addressed how the EU influenced opportunities for civil society actors by requiring their involvement in the implementation of EU acquis and providing other resources (Borzel and Buzogany 2010;Borzel 2010b). Other studies looked at how civil society actors from CEE adapt to new opportunities at the EU level (Pleines 2010).…”
Section: Europeanisation Of Interest Intermediationmentioning
confidence: 99%
“…Regarding the capacities of NGOs and interest associations in the democracies of Central and Eastern Europe (CEE) previous research showed that legacies of socialist times hinder them to act as watchdog organisations. Kutter and Trappmann (2010) and Pleines (2010) provide quite critical assessments of the ability of interest groups to use the EU system for their needs. According to their findings, legacies understood as social institutions, habits and discourses from the (post-)socialist period, compared with experiences made during the EU accession period and the various stimuli the EU provides to civil society, produce an ambiguous situation: some interest groups were able to adapt to the EU's expertise and bureaucracy-driven style of governance, while others still struggle with a new opportunity structure, an ongoing transformation of domestic state structures, clientelism and politicised bureaucracies.…”
Section: Theoretical Framework---civil Society and Its Potential For mentioning
confidence: 99%